2013
DOI: 10.4314/star.v2i2.98891
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water Handling Practices among Rural Communities of Dire Dawa Administrative Council, Dire Dawa, Ethiopia

Abstract: The aim of this study was to assess the impact of knowledge and hygienic practices of the community on bacteriological quality of drinking water at the source and point of use. community based cross-sectional study was conducted using questionnaire, inspection check list to observe the condition of water sources, and bacteriological water quality examination of sources and household containers. The study was conducted during February-May 2011 in rural Communitie Council. Three hundred eighty four households we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
5
6
0
Order By: Relevance
“…The study revealed that the most 789 (94.6%) commonly preferred type of water collection container was Jerrican. This finding is in agreement with similar study done in Dire Dawa rural communities and Kolladiba Town [13,12]. From the total respondents, the majority 579 (64.4%) and 743 (89.1%) were clean their container and wash their hands before collection of water respectively.…”
Section: Water Handling Practice Related To Water Collectionsupporting
confidence: 82%
See 1 more Smart Citation
“…The study revealed that the most 789 (94.6%) commonly preferred type of water collection container was Jerrican. This finding is in agreement with similar study done in Dire Dawa rural communities and Kolladiba Town [13,12]. From the total respondents, the majority 579 (64.4%) and 743 (89.1%) were clean their container and wash their hands before collection of water respectively.…”
Section: Water Handling Practice Related To Water Collectionsupporting
confidence: 82%
“…This is consistent with a study conducted in rural Dire Dawa communities, Ethiopia [12]. The majority of households 738 (88.5%) required less than 30 minutes to fetch drinking water and the mean per capita daily water consumption of the households was 10.2 (±4.4) liters.…”
Section: Water Source and Household Water Handling Practicesupporting
confidence: 78%
“…The main reason for letting the water be untreated before drinking is the expectation of the societies that the water may not be contaminated. It was possible to conclude that Fiche town communities' information about water treatment before drinking is comparable with the research result observed at Bona District (73%) and Dire Dawa Town (87%), where the majority of the households never treat water at home before drinking (Amenu et al 2013;Berhanu & Hailu 2015).…”
Section: Discussionsupporting
confidence: 74%
“…After use, drinking utensils were mostly kept on the table by 53% of the respondents while 26.1% left on the floor and 20.9% hanged it on the wall. e same study done at Jigjiga showed 62.2% of the households put on the table, 4.6% hanged on the wall, and 30.7% put on the floor [16], which is lower than the study conducted at Kolladiba town, which showed 75.5% put on the table, 9.7% put on the floor, and 4.8% hanged on the wall, respectively [17], which is higher than the same study held in Dire Dawa Adada and Legebira villages [8] and higher than the same study conducted at Tehuledere, Northeast Ethiopia, which showed only 51 (26.6%) of the households put water drawing utensils on tables and shelves while the majority (73.4%) put it on the floor, or hang it on the wall or leave it inside the container [9]. e current study indicates that protected hand-dug wells and shallow wells had significantly more E. coli (60% of tested samples) as compared to protected springs (25% of tested samples).…”
Section: Discussionmentioning
confidence: 89%
“…In Dire Dawa, Ethiopia, water handling practice in the Adada village shows that the most commonly preferred type of water collection container was jerry can which accounted for 59.37% followed by clay pots 40.63%. In relation to the way that the respondents withdrew water from containers, 8 (6.25%) preferred pouring and the remaining 93.75% by dipping [8].…”
Section: Introductionmentioning
confidence: 99%